Cerebrospinal Fluid Composition of Infants with Ischemic Stroke - Daniel, Katherine B.; Benjamin, Daniel K.; Smith, P. Brian; Cotten, C. Michael; Clark, Reese H.; Greenberg, Rachel G. (American Journal of Perinatology, 2025)
This study aimed to characterize the cerebrospinal fluid (CSF) of infants with stroke and compare those findings to the CSF of infants with bacterial meningitis and neither condition in the first 14 postnatal days.Cohort study of 30,092 infants who received a lumbar puncture in the first 14 postnatal days discharged from >400 neonatal intensive care units from 1997 to 2020. CSF parameters were compared between infants with stroke and bacterial meningitis using non-parametric hypothesis testing and quantile regression.Compared to infants with bacterial meningitis, infants with stroke had a significantly lower median protein concentration, higher median glucose concentration, higher median red blood cell count, and higher median monocyte count. Using quantile regression at the 75th percentile, infants with stroke had a significantly lower white blood cell count, segmented neutrophil count, and lymphocyte count than infants with bacterial meningitis.This study addresses the paucity of literature describing the CSF of infants with ischemic stroke. Knowledge of the differences in CSF parameters between infants with stroke and meningitis may allow for faster recognition and intervention before CSF culture results are available.
Keywords: infant; stroke; lumbar puncture; cerebrospinal fluid; meningitis